How to use storytelling in a strategic partnership between higher education and primary schools: writing for inclusion - Canals-Botines, Mireia; Raluy Alonso, Angel (Studi sulla Formazione/Open Journal of Education, 2021)
The European Project "Writing for Inclusion" (WIN) endeavours to raise awareness, to change perceptions and to provide resources on how to implement inclusion through storytelling in the language classroom. This research article sets the principles and tools of the project, while taking into account the creative process of building a story. The Project’s ultimate goal is to help build more inclusive education systems that cherish the values of diversity. Il progetto europeo "Writing for Inclusion" (WIN) ha il proposito di aumentare la consapevolezza, di cambiare percezioni e di fornire risorse su come implementare l'inclusione attraverso lo storytelling nelle classi di lingue. Questo articolo di ricerca definisce i principi e gli strumenti del progetto, tenendo conto del processo creativo di costruzione di una storia. L'obiettivo finale del progetto è aiutare a costruire sistemi educativi più inclusivi che apprezzino i valori della diversità.